Health related quality of life following open versus minimally invasive total gastrectomy for cancer: results from a randomized clinical trial - Wielen, Nicole van der; Daams, Freek; Rosati, Riccardo; Parise, Paolo; Weitz, Jürgen; Reißfelder, Christoph; Diez del Val, Ismael; Loureiro, Carlos; Parada-González, Purificación; Pintos-Martínez, Elena; Vallejo, Francisco Mateo; Achirica, Carlos Medina; et al. (European journal of surgical oncology, 2022)
Introduction - Minimally invasive techniques show improved short-term and comparable long-term outcomes compared to open techniques in the treatment of gastric cancer and improved survival has been seen with the implementation of multimodality treatment. Therefore, focus of research has shifted towards optimizing treatment regimens and improving quality of life. - Materials and methods - A randomized trial was performed in thirteen hospitals in Europe. Patients were randomized between open total gastrectomy (OTG) or minimally invasive total gastrectomy (MITG) after neoadjuvant chemotherapy. This study investigated patient reported outcome measures (PROMs) on health-related quality of life (HRQoL) following OTG or MITG, using the Euro-Qol-5D (EQ-5D) and the European Organization for Research and Treatment of Cancer (EORTC) questionnaires, modules C30 and STO22. Due to multiple testing a p-value < 0.001 was deemed statistically significant. - Results - Between January 2015 and June 2018, 96 patients were included in this trial. Forty-nine patients were randomized to OTG and 47 to MITG. A response compliance of 80% was achieved for all PROMs. The EQ5D overall health score one year after surgery was 85 (60-90) in the open group and 68 (50-83.8) in the minimally invasive group (P = 0.049). The median EORTC-QLQ-C30 overall health score one year postoperatively was 83,3 (66,7-83,3) in the open group and 58,3 (35,4-66,7) in the minimally invasive group (P = 0.002). This was not statistically significant. - Conclusion - No differences were observed between open total gastrectomy and minimally invasive total gastrectomy regarding HRQoL data, collected using the EQ-5D, EORTC QLQ-C30 and EORTC-QLQ-STO22 questionnaires.
Online verfügbar: 30. August 2021, Artikelversion: 3. März 2022
Gesehen am 06.05.2024